Cost-effectiveness of childhood pneumococcal vaccination program in Ethiopia: results from a quasi-experimental evaluation - Tayue Tateke Kebede; Mikael Svensson; Adamu Addissie; Birger Trollfors; Rune Andersson (BMC, 2019)
Abstract Background Ethiopia was among the 15 countries that, together accounted for 64% of the world's severe episodes of pneumonia among children below the age of 5 in 2011. To reduce this burden, the 10-valent pneumococcal conjugate vaccine (PCV 10) was introduced into the general childhood national immunization program in Ethiopia in 2011. However, there is little evidence on its cost-effectiveness, and the aim of this study was to estimate the cost-effectiveness of the introduction of PCV 10 vaccination in the Ethiopian setting. Methods The cost-effectiveness analysis was carried out based on a quasi-experimental evaluation of implementing PCV 10 at the Butajira rural health program site in Ethiopia. The intervention and the control groups consisted 876 and 1010 children, respectively. Using data from program site's surveillance system database as a framework, health outcome and vaccination data were collected from medical records, immunization registration books and reports. Disability- Adjusted Life Year (DALY) was a main health outcome metric complimented by incidence of acute lower respiratory infection/1000-person years. Vaccination and treatment costs were collected by document review and cross-sectional household survey. Results In the intervention cohort, 626 of 876 (71.5%) children received PCV 10 vaccination. Until the first year of life, the incidence of acute lower respiratory infection was higher in the intervention group. After the first year of life, the incidence rate was 35.2 per 1000-person years in the intervention group compared to 60.4 per 1000-person years in the control group. The incremental cost-effectiveness ratio (ICER) per averted DALY for the intervention group during the total follow-up period was (2013 US$) 394.3 (undiscounted) and 413.8 (discounted). The ICER per averted DALY excluding the first year of life was (2013 US$) 225 (undiscounted) and 292.7 (discounted). Conclusion Compared to the WHO's suggested cost-effectiveness threshold value, the results indicate that the general childhood PCV 10 vaccination was a cost-effective intervention in the Butajira rural health program site.